Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1111/j.1582-4934.2009.00742.x
|View full text |Cite
|
Sign up to set email alerts
|

Derivation of a novel undifferentiated human foetal phenotype in serum‐free cultures with BMP‐2

Abstract: Skeletal stem and progenitor populations provide a platform for cell-based tissue regeneration strategies. Optimized conditions for ex vivo expansion will be critical and use of serum-free culture may allow enhanced modelling of differentiation potential. Maintenance of human foetal femur-derived cells in a chemically defined medium (CDM) with activin A and fibroblast growth factor-2 generated a unique undifferentiated cell population in comparison to basal cultures, with significantly reduced amino acid deple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 89 publications
(118 reference statements)
0
3
0
Order By: Relevance
“…Foetal age was determined according to foot length and expressed as days post-conception. Samples ranged from 53 to 69 days (4 mm to 8.5 mm) [ 5 , 61 ]. Femora were dissected and surrounding soft tissues were removed by gentle rolling back and forth across sterile filter paper.…”
Section: Methodsmentioning
confidence: 99%
“…Foetal age was determined according to foot length and expressed as days post-conception. Samples ranged from 53 to 69 days (4 mm to 8.5 mm) [ 5 , 61 ]. Femora were dissected and surrounding soft tissues were removed by gentle rolling back and forth across sterile filter paper.…”
Section: Methodsmentioning
confidence: 99%
“…This result could be explained by the different composition of nutrients, for which those contained in αMEM are more appropriate for Characterization and regulation of human fetal bone cells the development and the physiology of fibroblastic-cell types. To date, only one other study has reported on the effect of several growth media on proliferation of fetal femur-derived cells (Mirmalek-Sani et al, 2009). However, these cells were taken at 8 weeks of development (only one in fetal development stage), which thus represents stem cells and not fetal (> 9 weeks) by definition.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, CSRP1 has been reported to participate in cell differentiation. For example, stimulation of human fetal femur-derived cells with fibroblast growth factor (FGF)-2 resulted into a significantly decreased CSRP1 level and reduced amino acid turnover, suggesting an undifferentiated cell status [ 7 ].…”
Section: Introductionmentioning
confidence: 99%